Sonographic assessment of fetal head and spine position before induction of labour (IOC) and obstetric outcomes : prospective study - Yaacob, Nor Azlina Che (2019)
OBJECTIVES:To study regarding the position of fetus by the position of the fetal head and the spine position (specifically fetal occiput posterior (OP) and spine posterior position) by ultrasonographyprior to induction of labour and during intrapartum and their adverse delivery outcomes. METHOD:This was a prospective study in which ultrasonographic fetal head and spine position were determined in350 women with singleton pregnancy immediately before induction of labour for various reasons at term. During early intrapartum, transabdominal sonography for fetal head and spine positionwere determinedand the progress of labour was monitored as usual. The outcomes of labour were measured. RESULTS: 350 pregnancies were evaluated before induction of labour and were followed up for first and second stages of labour until delivery. 329 women were then evaluated during the first stage and with 304 of them were evaluated during second stage. 24.3% of fetuses were found to be in an OP position and 16.3% of fetuses in the spine posterior position prior to induction of labour. However, the majority of OP and spine posterior then were rotated to an anterior position before delivery. There were 13 (3.7%) cases of OP and 11 (3.1%) cases of spine posterior position on ultrasound evaluation during second stage of labour. 296 (79.7%) cases delivered via vaginal delivery included ventouse (4.0%) and Forceps (0.9%). The incidence of EMLSCS was 54 (15.4%) amongst pregnant women. Out of 54 cases had EMLSCS, 15(17.6%) cases with occiput posterior position had undergone EMLSCS before induction of labour, followed by 8(15.1%) cases during first stage of labour and only 3(23.1%) cases during second stage of labour (Table 7). 9(15.8%) cases before induction of labour, 10 (29.4%) cases during first stage of labour and 4 (36.4%) cases during second stage of labour in relationship to spine posterior position had undergone EMLSCS (Table 8). There was no reported data regarding the position of occiput and spine position at delivery. Analysis failed to provide evidence of significant association between fetal occiput and fetal spine positions prior induction of labour with birth outcome as the p-values (p=>0.05) were not significant but fetal occiput and spine positions during first stage of labour (p=<0.001) and during second stage of labour (p=<0.001) and mode of delivery are dependent on one another. From Chi-square analysis, 12 of association or predictorsfactors that associated with birth outcome (VagD/Non-VagD), only 9 association factors (parity, birth weight, use of oxytocin during labour, duration of first stage of labour, time from start of IOL to delivery,fetal occiput position during first and second stage of labour and in fetal spine posterior during first and second stage of labour) with significant p-values (p=<0.05) correlated each other. CONCLUSION:There was no evidence of an association between any occiput positionsprior to induction labour with obstetric outcome (VagD/Non-VagD). However, this study showed statistically significant evidence that fetal occiput and spine posterior position during first and second stage of labour andincreased rate of caesarean section.